Genetic polymorphisms of the matrix metalloproteinase-3 (MMP-3) and tissue inhibitors of matrix metalloproteinases-1 (TIMP-1) modulate the development of ankylosing spondylitis. Issue 11 (19th November 2008) - Wei, J C-C; Lee, H-S; Chen, W-C; Shiu, L-J; Yang, S-F; Wong, R-H
Abstract : Background: The aetiology of ankylosing spondylitis (AS) remains unclear. Inflammation progresses to fibrosis and calcification of the spine and sacroiliac joints in AS development. Fibrosis results from excessive accumulations of the extracellular matrix (ECM). ECM turnover depends on the balance between matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs). Objective: To evaluate the effects of the MMP-3 -1171 and TIMP-1 372 T>C polymorphisms on the modified risk of AS. Methods: Genotypes of 241 patients with AS and 241 controls were identified by PCR. Disease activity and functional status were assessed by the Bath Ankylosing Spondylitis Activity Index (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Bath Ankylosing Spondylitis Global (BAS-G) Score. Results: MMP-3 6A/6 A carriers had a 2.41-fold (95% confidence interval (CI) 1.55 to 3.74) increased risk of AS compared with 6A/5A and 5A/5A carriers. TIMP-1 C alleles had a greater risk of AS, but this was not significant (odds ratio (OR) = 1.28, 95% CI 0.92 to 1.77). Pairwise analysis of the MMP-3/TIMP-1 alleles showed that 6A/C (OR = 3.23, 95% CI 1.50 to 6.95) and 6A/T (OR = 2.55, 95% CI 1.17 to 5.54) had a significantly greater risk of AS than the 5A/T alleles. After adjustment for the effects of age, gender and disease duration, the MMP-3/TIMP-1 5A/T alleles had the lowest BASDAI (p = 0.02), BASFI (p = 0.05) and BAS-G (p = 0.02) among all MMP-3/TIMP-1 alleles. Conclusion: The findings highlight the importance of the MMP-3 and TIMP-1 genes as crucial elements in AS development.